Gallnut tannic acid alleviates gut damage induced by Salmonella pullorum in broilers by enhancing barrier function and modulating microbiota - Zou, Junjie; Luan, Hongliang; Xi, Pengyuan; Xue, Junshu; Fan, Jiahao; Zhong, Xinyi; Zhou, Xun; Song, Xu; Zhao, Xinghong; Zou, Yuanfeng; Li, Lixia; Jia, Renyong; et al. (Frontiers in Veterinary Science, 2024)
Pullorum disease (PD) is a bacterial infection caused by Salmonella pullorum (S. pullorum) that affects poultry. It is highly infectious and often fatal. Antibiotics are currently the mainstay of prophylactic and therapeutic treatments for PD, but their use can lead to the development of resistance in pathogenic bacteria and disruption of the host's intestinal flora. We added neomycin sulfate and different doses of tannic acid (TA) to the drinking water of chicks at 3 days of age and infected them with PD by intraperitoneal injection of S. pullorum at 9 days of age. We analyzed intestinal histopathological changes and the expression of immune-related genes and proteins by using the plate smear method, histological staining, real-time fluorescence quantitative PCR, ELISA kits, and 16S rRNA Analysis of intestinal flora. The results demonstrate that S. pullorum induces alterations in the immune status and impairs the functionality of the liver and intestinal barrier. We found that tannic acid significantly ameliorated S. pullorum-induced liver and intestinal damage, protected the intestinal physical and chemical barriers, restored the intestinal immune barrier function, and regulated the intestinal flora. Our results showed that TA has good anti-diarrhoeal, growth-promoting, immune-regulating, intestinal barrier-protecting and intestinal flora-balancing effects, and the best effect was achieved at an additive dose of 0.2%.